Microorganisms, Tryptophan Metabolism, and Kynurenine Pathway: A Complex Interconnected Loop Influencing Human Health Status. (June 2019) - Dehhaghi, Mona; Kazemi Shariat Panahi, Hamed; Guillemin, Gilles J
The kynurenine pathway is important in cellular energy generation and limiting cellular ageing as it degrades about 90% of dietary tryptophan into the essential co-factor NAD + (nicotinamide adenine dinucleotide). Prior to the production of NAD +, various intermediate compounds with neuroactivity (kynurenic acid, quinolinic acid) or antioxidant activity (3-hydroxykynurenine, picolinic acid) are synthesized. The kynurenine metabolites can participate in numerous neurodegenerative disorders (Alzheimer disease, amyotrophic lateral sclerosis, Huntington disease, and Parkinson disease) or other diseases such as AIDS, cancer, cardiovascular diseases, inflammation, and irritable bowel syndrome. Recently, the role of gut in affecting the emotional and cognitive centres of the brain has attracted a great deal of attention. In this review, we focus on the bidirectional communication between the gut and the brain, known as the gut-brain axis. The interaction of components of this axis, namely, the gut, its microbiota, and gut pathogens; tryptophan; the kynurenine pathway on tryptophan availability; the regulation of kynurenine metabolite concentration; and diversity and population of gut microbiota, has been considered.